If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 = -2 + 3 Reorder the terms: -3 + x = -2 + 3 Combine like terms: -2 + 3 = 1 -3 + x = 1 Solving -3 + x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 1 + 3 Combine like terms: -3 + 3 = 0 0 + x = 1 + 3 x = 1 + 3 Combine like terms: 1 + 3 = 4 x = 4 Simplifying x = 4
| 2*x+3=5*x+17 | | 5(n-1)=55 | | 3x+5.4=(-6.3) | | 8x+y=240 | | 5y-17=-2 | | 5x/5y | | 10+11y+3y^2=0 | | 8-x=-2x+16 | | 6x+9=-6x-81 | | 2x^2+15x-2=0 | | a=17-b | | f(11)=2(11)+4 | | N/3-8=16 | | 8x+9y=96 | | f(11)=2x+4 | | (3^×)(9^2x)=1^3/9 | | y=0.25x+8 | | 5x+20+2x+11=115 | | 14n+3(n+5)=117 | | x^1/4(2x^3/4-x^1/4) | | (5v-3)(5v-2)=0 | | 100+2x+15-9x=5-7x+22-11x | | (1/3x)*(1/3x) | | T/8=2/9 | | 7a+12b=155c | | V/4-9=7 | | 4lnx=1.89 | | 9w^2+6w^3=0 | | 2x^3-15x^2+27x=0 | | 3x-7/12=1/6×(2x-3)-x-1/8 | | 2x+20=0.57 | | h=16t^2+80t+1 |